S16-2: Understanding Physical Activity Provision in Mental Health Services in Ireland (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Exercise is a robustly evidenced adjunct therapeutic for people accessing specialist mental health services. However, anecdotal accounts from the Irish context point to ad-hoc service provision, notwithstanding some examples of service innovation with respect to physical activity provision. The purpose of this work is: A. to describe the nature and scope of physical activity provision in Irish mental health services, in addition to the barriers and facilitators of exercise provision as described by service providers; B. to undertake an implementation focused case study of a novel pilot project where two Integrated Exercise Practitioners have been embedded into the mental health services. This case study seeks to document the Exercise Practitioner role, assess perceived effectiveness, and explore implementation to date.Methods: A mixed method, two-phased approach was undertaken. Phase 1 employed a national cross-sectional online survey evaluation. Here, participants were multi-disciplinary mental health services staff from the Republic of Ireland with knowledge regarding exercise provision in their service. Phase 2 was a descriptive qualitative case study of ‘physical activity service innovation’, framed by the RE-AIM framework, and aligned to the CFIR implementation science framework. Phase 2 participants included ‘integrated exercise practitioners’ or ‘management’ from the partner community based organisation, supported by policy and document analysis.Results: The survey evaluation included service providers (n = 45) from varying roles from different service types across Ireland. Almost 90% of respondents reported offering ‘some physical activity programmes within their services’. More than half cited mental health benefits as the main rationale for provision. Only 25% of respondents felt their programmes met service user needs; 67% of respondents referred their users to external programmes. Qualitative inquiry in the Phase 2 case study offers perceived reach, effectiveness, adoption, implementation, and maintenance insight into the integration of exercise practitioners in mental health services in Ireland.Conclusion: This work suggests there is urgent need to advance the standardisation of therapeutic physical activity provision in many mental health service contexts. We further offer implementation and scaling insight for the development of integrated exercise practitioners in mental health in the Irish context.Support/Funding Source: Co-funded by: Mental Health Ireland and The South East Technological University.